Correlation between saliva glycated and blood glycated proteins - Nakamoto, Ichiro (Springer-Verlag, 2003)
OBJECTIVES: Blood and saliva samples were obtained to examine if there is a correlation between saliva glycated protein and blood glycated protein. METHODS: Blood and saliva samples of 51 male workers were collected. The fructosamine and hydrazine methods were used to measure saliva glycated protein. HbA1c, fructosamine and blood glucose were measured as indices of blood glycated protein, and the correlation between blood glycated protein and saliva glycated protein was examined. RESULTS: Saliva fructosamine glycated protein showed a significant correlation with HbA1c and blood glucose (r=0.449; p=0.001 and r=0.445; p=0.001, respectively). No correlation was identified between saliva hydrazine glycated protein and the index of blood glycated protein. CONCLUSIONS: Blood glycated protein and blood glucose could be estimated by measuring saliva glycated protein.